2020
DOI: 10.1007/s40279-020-01400-x
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Hamstring Function Recovery After ACL Reconstruction

Abstract: It is important to optimise the functional recovery process in order to enhance patient outcomes after major injury such as anterior cruciate ligament reconstruction (ACLR). This requires in part more high-quality original research, but also an approach to translate existing research into practice to overcome the research to implementation barriers. This includes research on ACLR athletes, but also research on other pathologies, which with some modification can be valuable to the ACLR patient. One important co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 217 publications
(304 reference statements)
1
23
0
6
Order By: Relevance
“…Previous studies have emphasized the importance of hamstring muscle function recovery in patients who underwent ACLR, as it is associated with the occurrence of knee osteoarthritis and reinjury upon returning to sports. 5 Our results emphasize the role of quadriceps and hamstring muscle strength in achieving better subjective outcomes in patients undergoing ACLR.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have emphasized the importance of hamstring muscle function recovery in patients who underwent ACLR, as it is associated with the occurrence of knee osteoarthritis and reinjury upon returning to sports. 5 Our results emphasize the role of quadriceps and hamstring muscle strength in achieving better subjective outcomes in patients undergoing ACLR.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, previous studies have shown that the reconstructed leg demonstrates lower strength than the contralateral leg, emphasizing the importance of quadriceps and hamstring strength for knee movement control and functional performance. 2,3,27,37 Quadriceps symmetry has also been used as a prerequisite for a successful return to sports after ACLR. 8 These studies used the contralateral leg as a reference and did not analyze whether the contralateral muscle strength was normal.…”
mentioning
confidence: 99%
“…Thus, a focus should be put on improving hamstring strength in the rehabilitation process post ACL reconstruction which is in line with current approaches. [37] In addition, hamstring muscle loading has been demonstrated to reduce loading of the ACL. [38][39][40] For the male athletes, six out of the ten most impactful features are differences between advantageous and disadvantageous leg including both quadriceps and hamstrings.…”
Section: Return-to-sport Decision Rulesmentioning
confidence: 99%